The women in situation of gaslighting – risk identification in the work environment. (20th October 2021) - Dimitrova, D
Abstract: Background: As a contemporary form of "workplace harassment' (WH) is reported gaslighting. Preston Ni, defines it as 'A form of constant manipulation and brainwashing…' The phenomenon is presented as mainly affecting the woman in the workplace. The aim of the study is to determine and identify the risk of subjecting a woman in the workplace in Bulgaria to this form of psychological pressure gaslighting, in favor of building a risk reduction program cause. Methods: Empirical sociological research (ESR) among working women for period of 10 years in Sofia (around 2 million citizens), Bulgaria. An anonymous survey of 2, 000 working women between the ages of 30 and 65 was conducted. The questionnaire of the respondents with only more than 5 years of work experience are included. Results: Of the surveyed 25% are between 30-40 years, about 47% are 41-50 years, about 25% are 51-60 years and about 3% are 61-65 years. The result of the study indicates that mostly women between 41 and 50 years are subjected to psychological pressure by a man at work (about 45%), about 15% - are 51-60 years, only about 5% of women 31-40 years, and less 2% over 61. All of them are described as introverted. Mostly women with a high level of education have remained mentally resistant to gaslighting - about 35% of respondents, and less than 5% of them have shown higher creativity against the background of psychological pressure. In almost 1/3 of those subjected to prolonged mental harassment, were diagnosed for the first time, including: Hashimoto's thyroiditis (5%); arterial hypertension (about 10%); ischemic disease (about 15%). Half of them are presented with depression. Conclusions: Gaslighting is a hidden psychological violence against a female person based on hate speech and demonstration of power. Gaslighting is defined as a real risk among women, mostly of the introverted type. Emotional plasticity based on knowledge and smart has a positive effect in situation of gaslighting. Key messages: Gaslighting can lead to lack of confidence, clinical depression, distress and related physical illnesses. Early risk detection provides advantages for early reduction and optimization of the corporate culture of the department and the institution and in favor of building a risk reduction program.